2003
DOI: 10.1016/s0735-1097(03)00770-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coronary plaque color and morphology by lipid-lowering therapy with atorvastatin: serial evaluation by coronary angioscopy

Abstract: This is the first report clarifying detailed changes in coronary plaque by statin in humans. This study indicated that lipid-lowering therapy changes plaque color and morphology and should then lead to coronary plaque stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 24 publications
2
92
0
2
Order By: Relevance
“…Continuous strong-statin therapy for 12 months leads to a masked reduction of LDL-C levels and a yellow color of coronary plaques at non-culprit lesions 18) . In other words, aggressive LDL-C lowering (around 100 mg/dL) changed the average plaque color to light yellow, not intense yellow in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous strong-statin therapy for 12 months leads to a masked reduction of LDL-C levels and a yellow color of coronary plaques at non-culprit lesions 18) . In other words, aggressive LDL-C lowering (around 100 mg/dL) changed the average plaque color to light yellow, not intense yellow in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the power of serum levels of CRP in predicting disease activity should also be confirmed. Furthermore, the same authors have previously reported that statin therapy reduces the serum CRP level and angioscopic complexity of the plaques (the existence of the thrombus and the irregularity of the plaque) in nonculprit lesions (Takano et al, 2003). In this study, data from univariate logistic regression analyses indicated that both statin therapy and serum CRP level at follow-up are considered predictors of healing in nonculprit ruptured plaques.…”
Section: Soluble Biomarkersmentioning
confidence: 50%
“…26) These should make thin fibrous caps thicker and appear to reduce angioscopic yellow grade. 27) Recently, aspiration thrombectomies have been reported to be associated with decreased thrombi and clinical events. 28) Therefore, aggressive lipid-lowering therapy and volume reduction of the thrombus with thrombolysis or a thrombectomy before stenting may promote NSC over an intense yellow plaque with a thrombus.…”
Section: Discussionmentioning
confidence: 99%